Planetary period oscillations in Saturn's magnetosphere: Examining the relationship between abrupt changes in behavior and solar wind‐induced magnetospheric compressions and expansions. Issue 11 (21st November 2015) - Provan, G.; Tao, C.; Cowley, S. W. H.; Dougherty, M. K.; Coates, A. J.
Abstract: We examine planetary period oscillations (PPOs) observed in Saturn's magnetospheric magnetic field data from the time of Saturn's equinox in 2009. In particular, we focus on the time period commencing February 2011, when the oscillations started to display sudden and unexpected changes in behavior at ~100–200 day intervals. These were characterized by large simultaneous changes in the amplitude of the northern and southern PPO systems, together with small changes in period and jumps in phase. Nine significant abrupt changes have been observed in the postequinox interval to date, commencing as the Sun started to emerge from a long extended solar minimum. We perform a statistical study to determine whether these modulations in PPO behavior were associated with changes in the solar and/or upstream solar wind conditions. We report that the upstream solar wind conditions show elevated values of solar wind dynamic pressure and density around the time of PPO behavioral transitions, as opposed to before and after these times. We suggest that abrupt changes in PPO behavior may be related to significant changes in the size of the Saturnian magnetosphere in response to varying solar wind conditions. Key Points: Postequinox, Saturn's PPOs abruptly change behavior every ~100–200 days Enhanced solar wind dynamic pressure and density associated with these changes PPO behavior possibly modulated by changes in the size of Saturn's magnetosphere